Developing a market orientation - Deshpande, Rohit; Sage eBooks; Marketing Science Institute (Thousand Oaks, Calif. ; London : SAGE, 1999)
Defining market orientation as an organisational culture, a set of shared values and beliefs about putting the customer first in business planning, this book demonstrate its importance to strategy and tactics.
Papers originally published as Marketing Science Institute working papers.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Marketing research; Customer services; Corporate culture; Electronic books